Taking the law into their (virtual) hands a study on the digital vigilantism phenomenon on Facebook - Cox, Christine Ann Rovero
Digital vigilantism is an emerging process where citizens are "collectively offended by other citizen activity, and coordinate retaliation on mobile devices and social platforms" (Trottier, 2016). The multi-layered case of Christine Dacera, the Filipina flight attendant who was found dead on New Years 2021, is one such case that warrants the critical investigation of the role of Facebook in vigilant behaviors of Filipino users. Using an enhanced structuration lens and an affordances approach, this study asks the following: What are the practices of digital vigilantism manifested through the Facebook platform? What are the dominant affordances associated with the use of Facebook for digital vigilantism? What are the consequences of digital vigilantism in the context of everyday life and broader contexts of Philippine society? The chosen research method of netnography revealed that Facebook set the conditions for policing, rooted in moral affect and a sense of justice, and varying acts of denunciation, from shaming to doxxing to gender harassment. it found that the platform afforded users to speak to like-minded participants and have constant access to materials circulating within their networks, but also resulted in perhaps the formation of online echo chambers nad discourses rooted in misinformation, and connected discourses about the wider malfunctioning of the justice system and law enforcement institution.